ANALYZING THE REGIONAL DISPARITIES IN ROMANIA USING THE GINI INDEX AND THE LORENZ CURVE - Tiberiu Cristian AVRĂMESCU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
Inequality has recently become a topic generating increased interest both in political debates and in the academic environment. The issue of regional inequalities is systematically approached by specialists to provide the decision-makers with data and relevant information about the trends in this field, the elements that influence the level and evolution of disparities and to facilitate the evaluation of the effectiveness of the development strategies. The Gini index is one of the standard methods used in empirical research to analyze the territorial inequalities. Initially used to highlight the inequality of people's incomes, it has become more and more used in the field of spatial analyses.